1964
DOI: 10.1161/01.cir.29.3.393
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Studies of Pulmonary Edema at High Altitude

Abstract: Cardiac catheterization studies have been performed in four patients during acute pulmonary edema at an elevation of 12,300 feet in the central Peruvian Andes. Pulmonary hypertension, low cardiac output, arterial unsaturation, and low normal pulmonary artery wedge pressures were observed. Oxygen breathing was accompanied by a prompt, marked fall in pulmonary artery pressure and a slight rise in wedge pressure, indicating the presence of anoxic pulmonary arteriolar constriction. In one patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
1

Year Published

1968
1968
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(78 citation statements)
references
References 6 publications
2
74
1
Order By: Relevance
“…Consistently, pulmonary heamodynamic measurements at rest performed in early HAPE [17] and in all patients admitted to the hospital with HAPE [22][23][24][25][26][27], show that left atrial pressure, as assessed by occluded (or wedged) PAP, right atrial pressure and cardiac output are normal in HAPE. Recently, using the method of arterial occlusion, which is likely to measure pressures in vessels close to 100 mm in diameter [28], it was demonstrated that the pulmonary capillary pressure (Pc) is elevated in HAPE.…”
Section: Effects Of Acute Exposure To High Altitudesupporting
confidence: 56%
“…Consistently, pulmonary heamodynamic measurements at rest performed in early HAPE [17] and in all patients admitted to the hospital with HAPE [22][23][24][25][26][27], show that left atrial pressure, as assessed by occluded (or wedged) PAP, right atrial pressure and cardiac output are normal in HAPE. Recently, using the method of arterial occlusion, which is likely to measure pressures in vessels close to 100 mm in diameter [28], it was demonstrated that the pulmonary capillary pressure (Pc) is elevated in HAPE.…”
Section: Effects Of Acute Exposure To High Altitudesupporting
confidence: 56%
“…The crucial role of high pulmonary artery pressure is confirmed by elevated pulmonary artery pressures in patients with HAPE [2][3][4], enhanced pulmonary vasoconstrictive response in HAPE-susceptible subjects to acute hypoxia [5][6][7][8] or exercise in normoxia [6,7,9]. It is also confirmed by the fact that interventions decreasing pulmonary artery pressure are effective in the treatment [10,11] and prevention [4] of HAPE.…”
mentioning
confidence: 81%
“…Right heart catheterisation at high altitude revealed mean (range) pulmonary artery pressures of 60 mmHg, but normal pulmonary artery wedge pressures [58][59][60]. These pioneering studies put to rest the idea that HAPE was acute left heart failure at high altitude.…”
Section: Haemodynamicsmentioning
confidence: 99%
“…Bronchoalveolar lavage (BAL) shows a protein-rich exudate and mild alveolar haemorrhage, which initially is noninflammatory, but may progress after several days to a more inflammatory picture, as discussed later [55][56][57]. Echocardiographic and pulmonary artery catheterisation studies at high altitude show marked pulmonary hypertension [58][59][60].…”
Section: Hapementioning
confidence: 99%
See 1 more Smart Citation